Systemic BCG‐osis following intravesical BCG instillation for bladder carcinoma. Issue 10 (15th August 2017) - Liaw, Frank; Tan, Yan Yu; Hendry, David
Key Clinical Message: Intravesical instillation of Bacillus Calmette‐Guérin (BCG) has been shown to be an effective form of immunotherapy for bladder cancer. This case report describes a patient who develops systemic BCG‐osis following intravesical BCG instillation and demonstrates the importance of being aware of more severe complications associated with BCG immunotherapy. Abstract : Intravesical instillation of Bacillus Calmette‐Guérin (BCG) has been shown to be an effective form of immunotherapy for bladder cancer. This case report describes a patient who develops systemic BCG‐osis following intravesical BCG instillation and demonstrates the importance of being aware of more severe complications associated with BCG immunotherapy.